1-2/3(1/2+2q)=q/3

1 - 2/3(1/2 + 2q) = q/3

Now multiply by 3 on both sides,we get

3 * 1 - 2/3(1/2 + 2q) = 3 * q/3

Now

3 - 2(1/2 + 2q) = q

Now we solve the bracket, then

3 - 2[(1 + 4q)/2] = q

3 - (1 + 4q) = q

Now multiply minus int he bracket which will change the signs of terms in the bracket, then

3 - 1 - 4q = q

Now add 4q on both sides, we get

3 - 1 - 4q + 4q = q + 4q

3 - 1 = 5q

2 = 5q

Now divide by 5 on both sides,we get

2/5 = 5q/5

2/5 = q

Hence q = 2/5

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up